2013
DOI: 10.1186/1471-2407-13-285
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted vitamin E analogs inhibit breast cancer cell energy metabolism and promote cell death

Abstract: BackgroundRecent research has revealed that targeting mitochondrial bioenergetic metabolism is a promising chemotherapeutic strategy. Key to successful implementation of this chemotherapeutic strategy is the use of new and improved mitochondria-targeted cationic agents that selectively inhibit energy metabolism in breast cancer cells, while exerting little or no long-term cytotoxic effect in normal cells.MethodsIn this study, we investigated the cytotoxicity and alterations in bioenergetic metabolism induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
171
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(177 citation statements)
references
References 48 publications
4
171
0
2
Order By: Relevance
“…Previous studies also reported decreased ATP level in the mitochondria-targeted vitamin E analog (Mito-chromanol, Mito-ChM) and mitochondrial ErBB2 over-expressing cells. Decreased ATP level in MCF-7 and MDA-MB-231 cells identified to be effective in inhibiting energy metabolism in breast cancer cells and in mice xenografts [29, 30]. Thus, PP induces nonproductive mitochondrial respiration, as reported previously for cells with knockout LDH-A and for cells treated with FX-11 (LDH-A inhibitor) [14, 27].…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies also reported decreased ATP level in the mitochondria-targeted vitamin E analog (Mito-chromanol, Mito-ChM) and mitochondrial ErBB2 over-expressing cells. Decreased ATP level in MCF-7 and MDA-MB-231 cells identified to be effective in inhibiting energy metabolism in breast cancer cells and in mice xenografts [29, 30]. Thus, PP induces nonproductive mitochondrial respiration, as reported previously for cells with knockout LDH-A and for cells treated with FX-11 (LDH-A inhibitor) [14, 27].…”
Section: Discussionmentioning
confidence: 76%
“…The evidence accumulated to date indicates that mitochondria-associated apoptosis and energy metabolism could play important roles in cancer chemotherapy since the mitochondrion is also a crucial regulator of cell death [14][15][16][17]. Furthermore, recent studies conducted by several groups, including ours, have demonstrated that the mitochondria could be an alternative target to surmount multidrug resistance by suppressing the mitochondria's function of producing ATP and subsequently inhibiting the drug efflux function of P-gp protein [18,19].…”
Section: Introductionmentioning
confidence: 94%
“…[20][21][22][23] In particular, recent studies that target the glucose transporters have yielded a promising approach. Several analogs of glucose have been used in an attempt to reduce the glucose metabolism in cancer cells.…”
Section: Discussionmentioning
confidence: 99%